Minsan lang sila bata - Carolino, Ditsi; Archdiocese of Manila Labor Center (Philippines).; Ateneo Center for Social Policy and Public Affairs (Philippines). (Quezon City ACSPPA/AMLC, 1996)
A documentary on Filipino children who work in order to survive and to help their families. Tikboy, Delena and Bobby at an early age narrate their experience in working day and night.
VHS.
Tagapagkwento, Geejay Arriola.
Keywords: Children -- Employment -- Philippines; Child abuse -- Philippines; Child welfare -- Philippines; Children's rights